The function and the role of the mitochondrial glycerol-3-phosphate dehydrogenase in mammalian tissues - Mráček, Tomáš; Drahota, Zdeněk; Houštěk, Josef (Biochimica et biophysica acta, 2013)
Mitochondrial glycerol-3-phosphate dehydrogenase (mGPDH) is not included in the traditional textbook schemes of the respiratory chain, reflecting the fact that it is a non-standard, tissue-specific component of mammalian mitochondria. But despite its very simple structure, mGPDH is a very important enzyme of intermediary metabolism and as a component of glycerophosphate shuttle it functions at the crossroads of glycolysis, oxidative phosphorylation and fatty acid metabolism. In this review we summarize the present knowledge on the structure and regulation of mGPDH and discuss its metabolic functions, reactive oxygen species production and tissue and organ specific roles in mammalian mitochondria at physiological and pathological conditions.
Keywords: glycerolfosfátdehydrogenasa; reaktivní formy kyslíku; lidé; Allosteric Regulation; Oxidative Phosphorylation; Glycolysis; alosterická regulace; oxidativní fosforylace; Humans; Glycerolphosphate Dehydrogenase; mastné kyseliny; mitochondrie; sukcinátdehydrogenasa; Organ Specificity; glykolýza; Mitochondria; Succinate Dehydrogenase; zvířata; Animals; Fatty Acids; Reactive Oxygen Species; orgánová specificita